OPTIMALISASI PENGGUNAAN HARDWARE SERVER MEMPERGUNAKAN VIRTUALISASI SERVER DI SMAN 1 WONOSARI - Sriyanta Sriyanta; Wing Wahyu Winarno; Sudarmawan Sudarmawan (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2018)
The development of computer hardware progress is faster than software development, thus optimizing the use of hardware to achieve effectiveness and efficiency without reducing service to be things to consider. Schools with high specification hardware can be optimized for their use. One of the steps that can be taken to optimize the hardware is using virtual machine technology known as hypervisor. Virtual machine that functioned as a server called a virtual server. There are services from several independent server units that can be used in this technology. In addition to running it’s own service, the host server also run the virtual server services. The results of this study provide data from optimization of server utilization using virtual server as performance analysis, either from server host or virtual server. In general words by using virtual server technology can made server management by the school is relatively more simple and easier. It tend affects to the effective and efficient use of school resources in providing the services.